Diagnóstico tardio de síndrome de deleção 22q11.2 em criança com hipocalcemia sintomática: relato de caso - Camila Dalle Rocha; Maisa Andressa Sohn; Felipe Augusto Moreschi; Daniel Almeida do Valle; Mara Lúcia Schmitz Ferreira Santos; Vitor Costa Palazzo (Sociedade Brasileira de Pediatria, 2023)
22q11.2 Deletion Syndrome is the commonest microdeletion syndrome in humans and has a wide spec-trum of clinical manifestations, such as craniofacial dysmorphism, airway malformations, heart disease, renal malformations, hypoparathyroidism, neurological and behavioral disorders, immunodeficiencies and anomalies of the thymus. The broad phenotype spectrum makes the diagnosis more challenging, and an early identification allows not only the evaluation of comorbidities and interventions, but also adequate genetic counseling. Hypoparathyroidism manifested by symptomatic hypocalcemia is one of the clinical presentations of 22q11.2 Deletion Syndrome. This clinical case shows the diagnosis of 22q11.2 Deletion Syndrome in an 11-year-old child with symptomatic hypocalcemia and emphasizes the possibility of a late diagnosis of 22q11.2 Deletion Syndrome.